Influence of quenching temperature on piezoelectric and ferroelectrics properties in BaTiO3-Bi(Mg1/2Ti1/2)O3-BiFeO3 ceramics. (November 2018) - Nam, Hyunwook; Kim, Sangwook; Aizawa, Tomoya; Fujii, Ichiro; Ueno, Shintaro; Wada, Satoshi
Abstract: 0.3BaTiO3 -0.1Bi(Mg1/2 Ti1/2 )O3 -0.6BiFeO3 ceramics were fabricated by conventional solid-state reaction. Piezoelectric and ferroelectric properties were measured for as-sintered ceramic and ceramics quenched from temperatures of 600, 700, and 800 °C. The crystal system of the ceramics was pseudo-cubic in the as-sintered state and all the quenched states. Pinched P-E hysteresis loops were observed in the as-sintered sample. Ferroelectric P-E hysteresis loops and S-E curves were observed for the samples quenched from 700 and 800 °C. The electrical properties were enhanced with increasing quenching temperature, which could be attributed to an improved homogeneity of defect dipoles.